Real-world experience with secukinumab in the entire axial spondyloarthritis spectrum - Sivera, Francisca; Núñez-Monje, Victoria; Campos-Fernández, Cristina; Balaguer-Trull, Isabel; Robustillo-Villarino, Montserrat; Aguilar-Zamora, Marta; Garijo-Bufort, Marta; López-Gómez, Juan Miguel; Peña-González, Carolina; de la Morena, Isabel; Bedoya-Sanchís, Diego; Yankova-Komsalova, Liliya; et al. (Frontiers in Medicine, 2023)
Background Secukinumab is a biologic disease-modifying antirheumatic drug (bDMARD) that has demonstrated efficacy in the treatment of axial spondyloarthritis (axSpA, i.e., ankylosing spondylitis and non-radiographic axSpA) across various clinical trials. However, data of secukinumab in clinical practice is still limited. Here, we aimed to provide real-world data on secukinumab use, effectiveness, and persistence in axSpA. Patients and methods Retrospective, multicenter study of patients with a diagnosis of axSpA treated with secukinumab at 12 centers up to June 2021 in the Valencian Community (Spain). Information was gathered on BASDAI measurement, pain, patient and physician global assessment (ptGA, phGA) using a 100-mm visual analog scale (VAS), persistence and other secondary variables by treatment line (first, second, and ≥ third) for up to 24 months. Results 221 patients were included (69% men; mean age [standard deviation, SD]: 46.7 [12.1] years old). Secukinumab was used as a first-line bDMARD in 38% of patients, as a second-line in 34% and as a ≥ hird-line in 28%. The percentage of patients achieving low disease activity (BASDAI<4) increased from 9% at baseline to 48% at month 6 and was maintained (49%) up to month 24. Improvements in BASDAI were observed across all treatment lines: in naïve patients (month 6: −2.6; month 24: −2.7), in second-line (month 6: −1.9; month 24: −3.1), and in patients on third lines (month 6: −1.3; month 24: −1.7). Reductions in mean pain VAS (−23.3; −31.9), ptGA (−25.1; −31.9) and phGA (−25.1; −31) were also observed at 6 and 24 months. Secukinumab showed an overall 12-months persistence rate of 70% (95% confidence interval [CI]: 63–77%) and a 24-months persistence rate of 58% (95% CI, 51–66%). Patients receiving first-line secukinumab had the highest 24-months persistence rate (p = 0.05). Conclusion Secukinumab improved disease activity in axSpA patients, especially in naive, and second-line patients, which was accompanied by high persistence rates up to 24 months.